Distinct expression patterns of ICK/MAK/MOK protein kinases in the intestine implicate functional diversity. - Tufeng Chen; Di Wu; Christopher A Moskaluk; Zheng Fu (PLoS ONE, 2013)
ICK/MRK (intestinal cell kinase/MAK-related kinase), MAK (male germ cell-associated kinase), and MOK (MAPK/MAK/MRK-overlapping kinase) are closely related serine/threonine protein kinases in the protein kinome. The biological functions and regulatory mechanisms of the ICK/MAK/MOK family are still largely elusive. Despite significant similarities in their catalytic domains, they diverge markedly in the sequence and structural organization of their C-terminal non-catalytic domains, raising the question as to whether they have distinct, overlapping, or redundant biological functions. In order to gain insights into their biological activities and lay a fundamental groundwork for functional studies, we investigated the spatio-temporal distribution patterns and the expression dynamics of ICK/MAK/MOK protein kinases in the intestine. We found that ICK/MAK/MOK proteins display divergent expression patterns along the duodenum-to-colon axis and during postnatal murine development. Furthermore, they are differentially partitioned between intestinal epithelium and mesenchyme. A significant increase in the protein level of ICK, but not MAK, was induced in human primary colon cancer specimens. ICK protein level was up-regulated whereas MOK protein level was down-regulated in mouse intestinal adenomas as compared with their adjacent normal intestinal mucosa. These data suggest distinct roles for ICK/MAK/MOK protein kinases in the regulation of intestinal neoplasia. Taken together, our findings demonstrate that the expressions of ICK/MAK/MOK proteins in the intestinal tract can be differentially and dynamically regulated, implicating a significant functional diversity within this group of protein kinases.